FT-IR studies and excess thermodynamic properties of binary liquid mixtures 2-(2-butoxyethoxy) ethanol with 1-hexanol, 1-octanol and 1-decanol at different temperatures. (November 2018) - Kaur, Prabjot; Dubey, Gyan Prakash
Highlights: Thermodynamic, acoustic, transport and FT-IR spectroscopic study for the binary mixtures of 2-(2-butoxyethoxy) ethanol + 1-alcohols have been made. Excess molar volumes, deviation in isentropic compressibilities and deviation in speeds of sound were determined. Types of interactions were discussed. Abstract: In continuation to our prior investigational studies on the interactions between binary mixtures of alkoxy alkanols and alcohols, here, we report the thermo-physical properties and spectra analysis of 2-(2-butoxyethoxy) ethanol with CH3 (CH2 )3 OC2 H4 O(CH2 )2 OH, viz., 1-hexanol CH3 (CH2 )5 OH, 1-octanol CH3 (CH2 )7 OH and 1-decanol CH3 (CH2 )9 OH over the entire composition range at T  = (293.15, 298.15, 303.15, 308.15 and 313.15) K. The experimental data of densities and speeds of sound were used to calculate the values of excess functions and deviations in properties. The evaluated properties from experimental data have been construed in terms of the difference in the size of the molecule as well as the strength of specific and non-specific interactions between components of the mixture. The excess functions and their deviations have also been correlated using Redlich-Kister type polynomial equation by the method of least-squares for the estimation of the binary coefficients and the standard deviations. The FT-IR technique has been used to scrutinize the –OH interactions between the binary mixtures and inestimable to spot the influence on the structural variation in the alcohols.